Model Pembelajaran Fiqih di Kelas 1 MI Miftahul Huda Karangturi : Studi Lapangan - Mahmudi Mahmudi (Jurnal Budi Pekerti Agama Islam, 2023)
This study aims to describe the process of learning the subject of fiqh in class I MI Miftahul Huda Karangturi in the 2022/2023 academic year. This study uses a qualitative approach with a type of field research, where researchers directly collect data at the research location. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the fiqh learning process at MI Miftahul Huda Karangturi has been carried out systematically including planning, implementation, and evaluation. However, several obstacles were found in the learning process, such as the dominant use of the lecture method, low class management by teachers, low student interest in learning, limited teaching materials, and minimal use of learning media. The recommended efforts to overcome these obstacles include: the application of varied learning methods, improving teachers' abilities in managing classes and building emotional closeness with students, giving educational sanctions to students who are less focused, using interesting learning media, providing capable learning aids, and utilizing technology to support fiqh learning more optimally.